A new genus and species of cixiid planthopper (Hemiptera: Auchenorrhyncha: Fulgoroidea) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica - Bahder, Brian W. (2019)
Myxia belinda gen. et sp. nov. is established for a new taxon of Cixiidae in the tribe Oecleini collected from palms in Costa Rica. The new taxon was discovered while surveying palms for potential phytoplasma vectors. Placement in a new genus is supported by a 1,383 bp sequence of 18S that differs by 2.77% from Haplaxius, 5.20% from Myndus taffini, and 2.80% from Nymphomyndus caribbea. Intrageneric variation for 18S was found to be approximately 0.5% to 0.6% within Haplaxius. Generic level differences within the Oecleini for COI ranged from 15% to 17% with the novel taxon differing by about 16% from other genera. The new genus is most similar in appearance to Haplaxius but possesses striking sexual dimorphism, and the aedeagus is only partially surrounded by the phallobase (versus entirely enveloped in Haplaxius). The discovery of a novel taxon of cixiid on palms that is similar to Haplaxius is important because of the role that Haplaxius crudus plays in phytoplasma transmission in palm agro- and natural ecosystems.